MANAJEMEN BERBASIS POROS MARITIM KABINET KERJA PEMERINTAHAN JOKOWI- JUSUF KALLA - rosyid, moh (BISNIS, 2015)
The fact shows that 70 percent wide Indonesia is the sea. In geographic regions of the Unitary State of the Republic ofmainland only around 1.9 million kilo square meters, while the sovereignty of the sea consists of 3.1 million square kilometersand sea exclusive economic zone (ZEE) 2.7 km or 70 percent ofthe area of the archipelago in the form of the sea. The numberof large and small island as much as 17.500 island. A series of the island stretches from the east to the west as far as 6,400 km and almost 2,500 km from north to south. The potential for Coordinating Minister of Maritime law enforcement authorities recently have a work program be peneguhan maritime sovereignty, resource utilization, the infrastructure development and innovation development and maritime technology. The Program stresses that the maritime must be well managed to useful to the welfare of the people. The real form of the government in the form of maritime buildingutilization of maritime zones, treat maritime area, optimize the potential of waters environment, anticipation of evil in the seaand to optimize the performance of the national marine council. Various problems in the maritime governance circumventedAnalisis Manajemen Berbasis Poros Maritim by maintaining the sovereignty of the sea, in cooperation with the state adidaya, encouraged maritime industry, and take advantage of the waters as the lifeblood of the national economy.